Keterampilan Siswa dalam Pembelajaran Instalasi Penerangan Listrik Menggunakan Model Project-Based Learning - Deva Nur Avivah; Usmeldi Usmeldi (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2023)
This study was conducted to determine the practical skills of students by using a project-based learning model in Electrical Lighting Installation lessons in class XI TITL SMK Negeri 5 Padang. This type of research is experimental research with a pre-experimental design with a one-shot chase study. The research instrument used is a student skills assessment sheet using an assessment rubric collected through observation. Before conducting research, the skill assessment sheet was validated first by two experts, namely FT-UNP Electrical Engineering lecturers and Electrical Lighting Installation subject teachers. The population amounted to 73 students with a research sample of 13 people from class XI TITL 2 at SMK Negeri 5 Padang. The data analysis technique used is quantitative descriptive data analysis technique which includes mean, median, mode, standard deviation, frequency distribution table, and histogram. The results showed that students' practical skills were very good in Electrical Lighting Installation lessons using the project-based learning model.